Gait Training Methods and ChangesiIn Gait Parameters in Parkinson`s Disease (Literature Review) - Aušra Stuopelytė; Rasa Šakalienė (Lithuanian Sports University, 2020)
Parkinson's disease is a chronic progressive neurological disorder that can impact function to a variable degree. Changes in gait parameters are the most common signs of Parkinson's disease. Patients with Parkinson's disease walk with a reduced step length, step time, walking velocity and walking cadence, increased stride cycle time, coefficient of variation of the step amplitude and step time and increased risk to fall. So, various gait training methods are applied. The effect of rhythmic auditory stimulation on gait in Parkinson's disease patients is analysed. We can use various kinds of music, metronome, scansion and clapping as a rhythmic auditory stimulation.One of gait training methods in Parkinson's disease patients is treadmill training. There are attempts to combine treadmill training with transcranial magnetic stimulation and virtual reality. We can use Nordic walking method and because walking technique requires straight posture, trunk rotation, bigger step and heel stride. More often robot-assisted gait training is used in patients with Parkinson's disease gait training. The effect of dual-tasking and walking with music methods for gait and balance training in patients with Parkinson's disease is also analysed. This method requires participants to perform primary and secondary tasks at the same time. The secondary task can be cognitive or motor. Dual-tasking is widely analysed because opinions about applying this method are very controversial. Walking with music method is more often analysed in scientific literature. This method could not be compared to rhythmic auditory stimulation method because the latter requires precise walking to rhythm and walking with music method is oriented to emotional component (music is chosen according patients' music taste). As these methods are applied, we can see an increase in chosen walking and maximal walking velocities, step length and time, distance covered, and decrease in the coefficient of variation of the step time and turning time. Keywords: Gait impairments, walking velocity, rhythmic auditory stimulation.